Hippocampal Resting State Functional Connectivity in Patients With Schizophrenia and Unaffected Family Members - Edmiston, E. Kale; Song, Yanzhuo; Chang, Miao; Yin, Zhiyang; Zhou, Qian; Zhou, Yifang; Jiang, Xiaowei; Wei, Shengnan; Xu, Ke; Tang, Yanqing; Wang, Fei (Frontiers in Psychiatry, 2020)
The hippocampus is an important candidate region in the study of functional connectivity alterations in schizophrenia (SZ) given its role as a functional hub for multiple brain networks. Although studies have implicated the hippocampus in SZ, no studies have compared hippocampal functional connectivity in healthy participants, patients with SZ, and unaffected family members (UAFM). Patients and UAFM likely share biomarkers associated with susceptibility to SZ; the study of UAFM may also reveal compensatory markers. Patients with SZ, UAFM, and healthy control (HC) participants underwent resting state magnetic resonance imaging. We compared functional coupling with a hippocampus seed across the three groups. SZ and UAFM groups shared reductions in connectivity between the hippocampus and the striatum relative to HC. In contrast, UAFM showed increased hippocampal-cuneus connectivity relative to HC and SZ. Hippocampal-striatal rsFC may be associated with familial susceptibility to SZ, while hippocampal-cuneus connectivity may be a compensatory mechanism in UAFM.